2023
DOI: 10.3389/fpls.2023.1255033
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering performance of bamboo leaves, and establishment of mathematical model for the distribution and introduction prediction of bamboos

Yufang Wu,
Jing Li,
Lixia Yu
et al.

Abstract: Bamboo has great economic values and is used extensively in many industries, and their natural distribution range was divided into 12 zones in China according to the temperature of their geographical distribution in previous works. Different bamboo species had significantly different abilities in low-temperature tolerance, which need to be considered carefully during ex-situ introduction. In this paper, we observed and evaluated the low-temperature damage of 19 bamboo species in winter, and measured the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, the low activities of GR and GPX and the achievement of the highest GSH/GSSG ratio suggested that the GSH-GSSG cycle did not play a key role in ROS scavenging or resistance against freezing damage caused by the sudden snowfall in the Phyllostachys leaves (Figure 5). Additionally, our previous studies showed that the anatomical characteristics of Phyllostachys leaves significantly contributed to their cold tolerance [65]. DHAR plays a crucial role in regulating cellular AsA redox homeostasis by regenerating AsA from its oxidized state, which is essential for tolerance to various abiotic stresses [35].…”
Section: Effect Of Sudden Snowfall On the Asa-gsh System In The Leave...mentioning
confidence: 99%
“…Meanwhile, the low activities of GR and GPX and the achievement of the highest GSH/GSSG ratio suggested that the GSH-GSSG cycle did not play a key role in ROS scavenging or resistance against freezing damage caused by the sudden snowfall in the Phyllostachys leaves (Figure 5). Additionally, our previous studies showed that the anatomical characteristics of Phyllostachys leaves significantly contributed to their cold tolerance [65]. DHAR plays a crucial role in regulating cellular AsA redox homeostasis by regenerating AsA from its oxidized state, which is essential for tolerance to various abiotic stresses [35].…”
Section: Effect Of Sudden Snowfall On the Asa-gsh System In The Leave...mentioning
confidence: 99%
“…There exists a total area of 13900 hectares of natural Q. tumidinoda resources in Daguan County. This area accounts for 59% of the global total area of natural Q. tumidinoda , which amounts to 23560 hectares ( Dong, 2019 ; Wu et al., 2023b ). The highly raised nodes on the culms of Q. tumidinoda make it an excellent material for crafting walking sticks, bamboo handicrafts, and round bamboo furniture ( Yiyuan et al., 2020 ; Li et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%